Between two legal regimes, what has changed in the curriculum of initial teacher education in Portugal? - Teresa Teixeira Lopo (Arizona State University, 2016)
This paper analyzes, in a comprehensive perspective, the changes in the curriculum of the initial teacher education for the 1st cycle of basic education, grade level that in Portugal covers the first four years of compulsory education, between two legal regimes of professional qualification for teaching: the first, established in 2007 and due to the legislative reform required by the Bologna Process, the second, set up in 2014 and involving new changes, from the academic year 2015/2016, in the duration of the cycles of study, in its curricular organisation and training components. The results of our analysis suggest that the changes introduced in 2014 stem from a narrow reading, either of the results of the national research on initial teacher education, either of the recommendations from the studies and the international reports on comparative analysis that are invoked in this legal text to justify, precisely, such amendments.